2023
DOI: 10.1101/2023.02.15.528606
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strengthening connectivity between premotor and motor cortex increases inter-areal communication in the human brain

Abstract: The ventral premotor cortex (PMv) is an important component of cortico-cortical pathways mediating prefrontal control over primary motor cortex (M1) function. Paired associative stimulation (ccPAS) is known to change PMv influence over M1 in humans, which manifests differently depending on the behavioural context. Here we show that these changes in influence are functionally linked to PMv-M1 phase synchrony changes induced by repeated paired stimulation of the two areas. PMv-to-M1 ccPAS leads to increased phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Sensor differences with z-values corresponding to p<0.05 were retained as significant. The connectivity index of each condition was then estimated using the formula: CI = sig_pos/ sp_total, where sig_pos are connections that are significantly higher after FEF-TMS with respect to M1foot-TMS, and sp_tot are all possible connections (68,69). Furthermore, another permutation test was introduced to calculate the significance threshold for CI.…”
Section: Connectivity Changes: Effects Of Fef-tms (Vs Control-tms) On...mentioning
confidence: 99%
“…Sensor differences with z-values corresponding to p<0.05 were retained as significant. The connectivity index of each condition was then estimated using the formula: CI = sig_pos/ sp_total, where sig_pos are connections that are significantly higher after FEF-TMS with respect to M1foot-TMS, and sp_tot are all possible connections (68,69). Furthermore, another permutation test was introduced to calculate the significance threshold for CI.…”
Section: Connectivity Changes: Effects Of Fef-tms (Vs Control-tms) On...mentioning
confidence: 99%
“…For example, recent work assessing variability of M1 iTBS has suggested that the ability of iTBS to engage neural oscillations in the β range (13-30 Hz) may be an important predictor of the neuroplastic response to iTBS (Leodori et al, 2021). Enhancing premotor-M1 communication using cortico-cortical paired associated stimulation (ccPAS) has been recently shown to improve the synchronisation of neural oscillations (which is thought to mediate neuronal communication and plasticity) in the β range (Trajkovic et al, 2023).…”
Section: Pmd and M1 Influence On I-wave Recruitment In Young And Olde...mentioning
confidence: 99%
“…PMv activity is necessary for various grasping movements, exerting a substantial excitatory or inhibitory influence on M1 during these actions (Casarotto, Dolfini, Fadiga et al., 2023). Previous research has demonstrated that the PMv to M1 pathway is important for movement planning and control, and this inter‐areal communication can be modulated by ccPAS interventions with stimulation applied to PMv 6–8 ms prior to M1 (Sel, 2021; Trajkovic, 2023). Related to the findings by Trajkovic et al.…”
Section: Introductionmentioning
confidence: 99%
“…and Sel et al., Casarotto et al. recently demonstrated that the direction of TMS current over M1 (A‐P or P‐A) during ccPAS can affect post‐intervention measures (Casarotto, Dolfini, Cardellicchio et al., 2023; Sel et al., 2021; Trajkovic et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation